2003
DOI: 10.1039/b304583h
|View full text |Cite
|
Sign up to set email alerts
|

Practical field application of a novel BOD monitoring system

Abstract: A biochemical oxygen demand (BOD) monitoring system, based on electrochemically-active bacteria in combination with a microbial fuel cell, has been developed for the purpose of on-site, on-line and real-time monitoring of practical wastewater. A microbial fuel cell that had been enriched with electrochemically-active bacteria was used as the basis of the measurement system. When synthetic wastewater was fed to the system, the current generation pattern and its Coulombic yield were found to be dependent on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 12 publications
2
31
0
Order By: Relevance
“…The water to be analyzed is fed to the anode chamber where a biofilm on the anode surface converts organics into an electric current. An aerated buffer solution is fed to the cathode chamber where oxygen is reduced to water on the cathode surface Kim et al, 2003aKim et al, , 2003bMoon et al, 2004). Kumlanghan et al (2007) used a similar MFC setup, but instead of enriching a bioelectrochemically active culture on the anode, a stable anaerobic microbial consortium was maintained in a separate reactor, which was fed to the MFC for each analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The water to be analyzed is fed to the anode chamber where a biofilm on the anode surface converts organics into an electric current. An aerated buffer solution is fed to the cathode chamber where oxygen is reduced to water on the cathode surface Kim et al, 2003aKim et al, , 2003bMoon et al, 2004). Kumlanghan et al (2007) used a similar MFC setup, but instead of enriching a bioelectrochemically active culture on the anode, a stable anaerobic microbial consortium was maintained in a separate reactor, which was fed to the MFC for each analysis.…”
Section: Introductionmentioning
confidence: 99%
“…From day 2 onward, lactic acid concentrations decreased, with reductions of 14, 31, 54, and 71% with aeration of 0.2, 0.4, 0.8, and 1.0 vvm, respectively, by day 8. Fermentation of soybeans with R. oligosporus for tempeh production confirms that this fungal species is able to degrade lactic acid [83]. Fungal cultivation of settled thin-stillage supernatant improved lactic acid biodegradation, with 60% removal in 5 d with 0.8-vvm aeration (as compared to 54% with thin stillage particles).…”
Section: Organic Acids and Glycerol Removalmentioning
confidence: 73%
“…Kim et al [18] reported that their MFC BOD sensor remained stable for five years, but provided little evidence to support their claim. In particular, re-calibration was not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…MFC BOD sensors are quick and portable, and contain a mixed population of microorganisms (by using environmental inoculum from a wastewater reclamation plant in Singapore) able to oxidize a wide range of substrates [1,18]. Yet the design and operation conditions as reported in the literature are suboptimal, consisting of two-chambered MFC systems [13,14] functioning in batch mode [15,16,17].…”
Section: Introductionmentioning
confidence: 99%